2011
DOI: 10.1371/journal.pone.0020797
|View full text |Cite
|
Sign up to set email alerts
|

Pop Up Satellite Tags Impair Swimming Performance and Energetics of the European Eel (Anguilla anguilla)

Abstract: Pop-up satellite archival tags (PSATs) have recently been applied in attempts to follow the oceanic spawning migration of the European eel. PSATs are quite large, and in all likelihood their hydraulic drag constitutes an additional cost during swimming, which remains to be quantified, as does the potential implication for successful migration. Silver eels (LT = 598.6±29 mm SD, N = 9) were subjected to swimming trials in a Steffensen-type swim tunnel at increasing speeds of 0.3–0.9 body lengths s−1, first witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 49 publications
9
68
3
Order By: Relevance
“…The average speed is greater than that reported in previous studies of oceanic eel migration (Aarestrup et al 2009) and may reflect the greater spatial accuracy with which we reconstructed the migration route. These data also suggest that the swimming ability of eels was not significantly compromised by the tag or the tagging procedure (Methling et al 2011) and, as suggested in previous studies, provides optimism that tracking the full journey to the Sargasso Sea will be possible with further improvements in tag technology.…”
Section: Migration Speedssupporting
confidence: 78%
“…The average speed is greater than that reported in previous studies of oceanic eel migration (Aarestrup et al 2009) and may reflect the greater spatial accuracy with which we reconstructed the migration route. These data also suggest that the swimming ability of eels was not significantly compromised by the tag or the tagging procedure (Methling et al 2011) and, as suggested in previous studies, provides optimism that tracking the full journey to the Sargasso Sea will be possible with further improvements in tag technology.…”
Section: Migration Speedssupporting
confidence: 78%
“…However, for larger PSAT tags (2-3 % tag/bm), several studies have reported strong effects on swimming performance of eels, including up to three-fold increases in energy cost of transport [69][70][71]. Using spherical PSAT dummies of varying sizes, in a series of respirometry measurements and kinematic analyses, Tudorache et al [71] suggested that the optimal location for single point attachment of PSAT tags is more anterior than at the middle of the body length in eels.…”
Section: Swimming Performancementioning
confidence: 99%
“…We expected that frequency, amplitude and speed would be adjusted to maintain efficiency or a given St in low-and high-drag conditions. Some swimmers are able to compensate and maintain St (Noren et al 2011, Nudds et al 2014, whereas others have significantly greater and suboptimal St with drag loading (Lang & Daybell 1963;Methling et al 2011). In this study, the St of right whale Eg 3911 was significantly lower on descent than ascent, but did not change significantly following removal of entangling fishing gear (Fig.…”
Section: Changes In Efficiencymentioning
confidence: 52%
“…Here, we examine tag data from these 2 entangled whales with differences in natural and added drag and buoyant forces, manipulated during disentanglement procedures, with the expectations that: (1) fluke strokes and swimming speed would be altered to maintain normal power output under high drag loading conditions (Skrovan et al 1999, Simon et al 2012, van der Hoop et al 2014a; (2) individuals should take advantage of added buoyancy, reducing thrust and increasing speed in the buoyancy-aided direction (Aoki et al 2011, Miller et al 2012, Nousek-Mc Gregor et al 2014; and (3) swimming efficiency would be reduced when entangled. Together, these hypotheses address whether animals maintain optimal swimming under drag loading, or whether physiological and anatomical constraints limit the plasticity of these parameters and the maintenance of efficient swimming techniques under high loading conditions (Methling et al 2011, Nudds et al 2014, Shimojo et al 2014.…”
Section: Introductionmentioning
confidence: 99%